David Hancock: Oceans of wine: Madeira and the Emergence of American Trade and Taste. New Haven & London, Yale University Press, 2009, 632 págs. - Lamikiz Gorostiaga, Xabier (Investigaciones de Historia Económica, 2019)
Sin resumen